The printing of Munshi Abdullah's edition of the sejarah Melayu in Singapore - Ibrahim, I. (University of Malaya Library, 1986)
The printing of the first edition of Sejarah Melayu was carried out by Munsyi Abdullah in Singapore. The bibliographic details on this first edition is not commonly known as it was not indicated in the book itself. Studying evidence from photocopy and microfilm version of this book held at the University of Malaya Library and information collated from other sources, a clearer picture can be constructed about the background of its printing. This study proposes that the printing date of this first edition was not 1831 (as commonly assumed) but ten years later in 1840 or 1841.